Neonatal outcomes associated with obstetric interventions performed during labor in nulliparous women - Paloma Gabrielly Amorim Monteiro; Tatiane da Silva Coelho; Adriana Moreno de Lima; Uly Reis Ferreira; Maria Salete Barbosa Monteiro; Cinthia Maria Gomes da Costa Escoto Esteche; Ana Kelve de Castro Damasceno (Rev Rene)
Objective: to analyze neonatal outcomes associated with obstetric interventions performed during labor in low-risk nulliparous women. Methods: a cross-sectional observational study of 534 low-risk nulliparous women. Results: interruption of skin-to-skin contact after delivery was shown to be associated with obstetric interventions such as cardiotocography at admission, oxytocin in labor, amniotomy, and episiotomy. The need for positive pressure ventilation and oxygen therapy was associated with the encouragement of the Valsalva maneuver; the performance of this maneuver was also associated with interventions such as amniotomy, episiotomy and directed pulling. Conclusion: the study showed that the use of obstetric interventions during labor in low-risk women is associated with unfavorable neonatal outcomes that lead to the need for further interventions after delivery.